Character education in English package books for Islamic Junior High School students - Wahyuningsih Usadiati; Maida Norahmi (Journal on English as a Foreign Language, 2019)
The research is an inventory aimed at identifying and categorizing the character values in the English package books for students of Islamic Junior High School or Madrasah Tsanawiyah by considering their relevance to Islamic character values in the Quran and Hadits. The method used was content analysis following Bogdan and Biklen model by analyzing, grouping, sorting, and synthesizing the values taken from the package books to draw the patterns.  The patterns were discussed to conclude the final findings to be disseminated as the list of inventory.  The main data source was the English package books published by the government and the supporting data were the Core Competencies taken from Curriculum 2013 for Junior High School (SMP) and Madrasah Tsanawiyah (MTs) or Islamic Junior High School students. There are 10 values inserted in the package books that are relevant to the Islamic religious characters. The result showed various English expressions relevant to Islamic character values which have a long-term and sustainable effect as a reference for character building by English teachers in developing English supplementary materials for Islamic Junior High School students.